THE DEVELOPMENT INSTRUMENTS NATURALIST EARLY CHILDHOOD INTELLIGENCE IN EASTERN DISTRICT LUWU SOUTH SULAWESI PROVINCE - Ismail, Afandi; Tjalla, Awaluddin; Triana, Dinni Devy (Universitas Panca Sakti Bekasi, 2024)
The purpose of this development is to develop instruments Early Childhood Naturalist intelligence in East Luwu Regency South Sulawesi Province, valid and reliable. Operationally, this study is to describe (1) the development of instruments Naturalist intelligence Childhood, (2) constructing instruments Naturalist intelligence Early Childhood valid and reliable. This study was conducted in 10 public elementary schools in East Luwu Regency. Conceptually, construct naturalistic intelligence consists of seven dimensions, namely: (1) Sensitivity to nature, (2) ability to identify, classify and distinguish some species in large quantities, including flora, fauna and the environment, (3) The food chain, (4) Love of nature, animals and plants, (5) the ability to distinguish living matter with inanimate objects, (6) Interested in the world of animals or plants, and (7) Care about the environment, pay attention to nature and easily adapts to nature. Based on the review and validation of expert panelists interrater coefficient values obtained for the seven dimensions are reliable. Data analysis using SEM with 8.80 lisrel software model of first order confirmatory analysis. In the first empirical test validation results are 26 items that dropped while in the second stage of empirical testing of all items that as many as 29 items were declared valid. Reliability test results construct empirical tests first and second stages show all dimensions reliable. At GOF size mostly shows a good fit (good fit), so the instrument Naturalist intelligence Childhood in East Luwu regency of South Sulawesi Province has developed a valid and reliable and can be used as a measuring tool that is reliable.